Islamic Spiritual Care with Murottal for Reducing Anxiety and Depression in Coronary Heart Disease Patients: A Comprehensive Systematic Review - Wisuda, Aris Citra; Sansuwito, Tukimin bin; Suraya, Citra (YCAB Publisher, 2024)
Background:Spiritual care is a vital aspect of the nursing process, particularly for palliative patients such as those with Coronary heart disease. While pharmacological and medical interventions remain paramount for managing heart conditions, the efficacy of Islamic spiritual therapy with Murottal has also been significant. Research has demonstrated its notable influence on patients' quality of life, particularly in mitigating anxiety and depression. Objective:This study aims to conduct a systematic review to explore the role of Islamic spirituality in nursing, specifically through Murottal recitations, and its impact on anxiety and depression among Coronary heart disease patients. Method:Employing a systematic review design, we utilized various electronic databases including PubMed, ProQuest, Science Direct, DOAJ, Wiley, Garuda, and secondary PubMed-indexed sources from 2018 to 2023. Inclusion criteria comprised studies with a clear definition of spiritual care involving Murottal in nursing, confirmed Coronary heart disease diagnoses, and reporting outcomes such as the incidence of death, cardiovascular outcomes, and quality of life. Result:The search focused on examining the correlation between Islamic spiritual care with Murottal and the quality of life in patients with coronary heart disease. Following a rigorous methodology, which included study selection, critical appraisal, data extraction, and synthesis, the search yielded 1,286 articles, with seven meeting the inclusion criteria. Analysis and categorization of these articles based on evidence level and recommendations revealed a consistent association between Islamic spiritual care with Murottal and reduced anxiety and depression in Coronary heart disease patients. However, heterogeneity was observed in research instruments, implementation duration, and outcomes. Conclusion:The conclusive evidence from this review supports the notion that Islamic spiritual care, particularly through Murottal recitations, significantly impacts the quality of life among Coronary heart disease patients. Keywords: Anxiety, Coronary Heart Disease, Depression, Murottal, Spiritual Care